A1.85 Can rituximab treatment in rheumatoid arthritis patients decrease cardiovascular risk?. (31st January 2014) - Gudu, Tania; Mazilu, Diana; Peltea, Alexandra; Opris, Daniela; Ionescu, Ruxandra
Abstract : Background and Objectives: Rheumatoid arthritis (RA) is not only a chronic inflammatory joint disease, but also a condition associated with a high risk for cardiovascular diseases, mostly due to the inflammatory burden. Therefore, EULAR recommends using a modified assessment of cardiovascular risk, mSCORE which is obtained by multiplying SCORE by 1.5. The objective of this study is to evaluate the impact of rituximab on cardiovascular risk. Materials and Methods: 42 RA patients initiating rituximab in 2010 were included and were prospectively followed for 18 months. They all had active disease and were non-responders to DMARD therapy (synthetic and/or biologic). The cardiovascular risk was evaluated by mSCORE (at baseline and at 18 months). Response to rituximab therapy was assessed using EULAR response at 6 months (ER6) and at 18 months (ER18). The study is still ongoing, in order to assess long-term impact of rituximab on cardiovascular risk in RA patients. Results: ER at 6 months was negatively correlated to mSCORE at 18 months (r = -0.353, p = 0.032). Disease duration seems to have a high impact on cardiovascular risk (correlation with mSCORE at baseline: r = 0.993, p < 0.001, with mSCORE at 18 months: r = 0.668, p < 0.001). Drugs such as statins and methotrexate which are known to be protective for cardiovascular diseases do not influence mSCORE at 18 months (r = 0.191, p = 0.239, respectively r = -0, 156, p = 0.337). Cardiovascular risk in patients initiating rituximab is still high after a year and a half of treatment, regardless of using cardiovascular protective drugs. The negative correlation between ER6 and mSCORE at 18 months suggests that anti CD20 therapy might be useful for decreasing cardiovascular burden in RA patients. Though, in patients with a longer duration of disease, mSCORE remains high after 18 months of treatment. Conclusions: Although an early good clinical and biological response at 6 months to rituximab therapy seems to decrease the cardiovascular risk after 18 months of treatment, the cardiovascular burden is still high (even with protective drugs), probably due to previous inflammatory status.